2022
DOI: 10.1088/1742-6596/2151/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

How do NEWA and ERA5 compare for assessing offshore wind resources and wind farm siting conditions?

Abstract: In advance to the construction of a wind farm, a wind resource assessment is performed, often by the use of wind atlas data. Two widely used and publicly available numerical datasets, ERA5 and the recently created NEWA, are compared and evaluated regarding wind climatology, variability and extreme wind speeds using a comprehensive database with high quality offshore measurements. NEWA shows to be more accurate but less precise in terms of predicting mean wind speed and correlation coefficients. However, the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…ERA5 estimates of wind and wave conditions has been extensively independently evaluated and shown to exhibit relatively high fidelity (S. C. Pryor et al, 2020;Gramcianinov et al, 2020;Sharmar and Markina, 2020;Hallgren et al, 2020). However, past research has also indicated substantial spatiotemporal variability in the fidelity of ERA5 wind speed products of relevance to wind energy contexts (Pryor et al, 2020a;Kalverla et al, 2020;Meyer and Gottschall, 2022;Knoop et al, 2020). Here we are using ERA5 output to (i) examine climatological variability and thus contextualize the short observational records, (ii) provide context for the spatial decay of association manifest in the remote sensing observations, and (iii) quantify the bias in annual mean wind speeds due to seasonal bias in lidar data availability.…”
Section: Era5 Reanalysismentioning
confidence: 99%
“…ERA5 estimates of wind and wave conditions has been extensively independently evaluated and shown to exhibit relatively high fidelity (S. C. Pryor et al, 2020;Gramcianinov et al, 2020;Sharmar and Markina, 2020;Hallgren et al, 2020). However, past research has also indicated substantial spatiotemporal variability in the fidelity of ERA5 wind speed products of relevance to wind energy contexts (Pryor et al, 2020a;Kalverla et al, 2020;Meyer and Gottschall, 2022;Knoop et al, 2020). Here we are using ERA5 output to (i) examine climatological variability and thus contextualize the short observational records, (ii) provide context for the spatial decay of association manifest in the remote sensing observations, and (iii) quantify the bias in annual mean wind speeds due to seasonal bias in lidar data availability.…”
Section: Era5 Reanalysismentioning
confidence: 99%